Social and Institutional Dimensions of Axel Honneth’s Theory of Recognition (by Marcin J. Byczyński, 2021). A Book Review with a Contextual ‘Surplus’ - Nowak, Ewa (ETHICS IN PROGRESS, 2022)
The review addresses the recent monograph Social and Institutional Dimensions of Axel Honneth’s Theory of Recognition by Marcin J. Byczyński (Łódź University Press, Jurisprudence Series, Vol. 17/2021, pp. 1–273). Jakub Kloc-Konkołowicz was the external reviewer of the doctoral dissertation which gave rise to the book. The essential contributions of this book are discussed against the background of former and pioneering recognition research from the Polish context, including this by Jakub Kloc-Konkołowicz and Marek Siemek. In addition, they are supplemented by Hegel’s three rights of freedom and further vital themes. This provides the following review with a contextual ‘surplus.’ Byczyński’s monograph considerably advances an important Warsaw-Poznań research strand and is notable for its originality among the books devoted to Honneth’s Theory of Recognition.